Tafsir Kontemporer Nusantara Studi Tafsir Juz ‘Amma As-Sirajul Wahhaj Karya M. Yunan Yusuf - Abu Maskur (AL-MUFASSIR, 2022)
Tafsir is one of the disciplines that are most in demand by the public, especially the Islamic community, so that it continues to develop both in the Middle East as the center of Islamic civilization and in other areas, such as in the Archipelago. This study aims to determine the method, style and systematic interpretation of one of the interpretations that emerged in the contemporary era in the archipelago, namely Tafsir Juz 'Amma As-Sirajul Wahhaj by M. Yunan Yusuf. The type of research used in this research is library research. The results found in the study show that the Tafsir Juz 'Amma As-Sirajul Wahhaj by M. Yunan Yusuf uses the tahlili method, which is a long explanation. In addition, the pattern in this interpretation is the style of al-adabi al-ijtima'i and 'ilmi, which focuses on contextualizing the contents of the Qur'an with the conditions faced by society and focuses on the approach of science (science). Meanwhile, the systematics used in this interpretation is an orderly systematic, following the procedures of scientific work